2005
DOI: 10.1152/ajpregu.00344.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on vasopressin-induced emesis in conscious dogs

Abstract: Although acupuncture has a significant clinical benefit, the mechanism of acupuncture remains unclear. Vasopressin, a posterior pituitary hormone, is involved in nausea and vomiting in humans and dogs. To investigate the antiemetic effects of acupuncture on vasopressin-induced emesis, gastroduodenal motor activity and the frequency of retching and vomiting were simultaneously recorded in conscious dogs. In seven dogs, four force transducers were implanted on the serosal surfaces of the gastric body, antrum, py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
(47 reference statements)
2
30
0
3
Order By: Relevance
“…EA at acupoints located on the back [bladder-21 (BL21)] were used for sham acupuncture. BL21 is located 1 cm lateral of the spinous process of the 12th thoracic vertebrae (45).…”
Section: Electroacupuncturementioning
confidence: 99%
See 2 more Smart Citations
“…EA at acupoints located on the back [bladder-21 (BL21)] were used for sham acupuncture. BL21 is located 1 cm lateral of the spinous process of the 12th thoracic vertebrae (45).…”
Section: Electroacupuncturementioning
confidence: 99%
“…It may be mediated via the neural reflex, and either the nociceptive or nonnociceptive afferent pathway is involved, which is correlated with distension volumes and visceral sensation (19). More recent studies showed that sympathovagal balance was altered in IBS patients (23,41,45), but it is not clear whether these activities are altered with RD.Acupuncture is a traditional Chinese medicine involving stimulation of the acupoints in the skin by thin, metallic needles that are manipulated manually or combined with electrical stimulation, a procedure referred to as electroacupuncture (EA). Acupressure is a noninvasive medical technique conducted by pressing on the acupoints with the fingers or by an embedded stud over the acupoints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the effect of acupuncture on the heart rate variability, it was concluded that this effect was associated with increased vagal activity. A central effect of electroacupuncture has also been suggested by Tatewaki et al [19] who demonstrated that electroacupuncture at PC6 reduced the number of retching and vomiting episodes following vasopressin injection in dogs, an anti-emetic effect which was abolished by pretreatment with naloxone. Whether this proves to be similar for humans is unknown.…”
Section: Discussionmentioning
confidence: 64%
“…[28,29] pobudzający wpływ akupunktury był hamowany właśnie przez atropinę i heksametonium, czyli znane parasympatykolityki. Okazało się jednak, że aktywujący wpływ akupunktury nie był obserwowany u szczurów po dokonanej wagotonii.…”
Section: Układ Przywspółczulny a Tempo Metabolizmu Energetycznegounclassified